2020
DOI: 10.18306/dlkxjz.2020.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Beijing urban spatial cognition based on follow-up investigations:Take graduate students in the University of Chinese Academy of Sciences as an example

Abstract: Beijing urban spatial cognition based on follow-up investigations: Take graduate students in the University of Chinese Academy of Sciences as an example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…This value did not include the EFW end use at household level (e.g., the energy for heating water, running washing machines, or dishwashers). A previous study by Li (2012) estimated the household-level EFW of Beijing in 2010 as 4.88 billion kWh, which is greater than the EFW in this study. But it is still debated (see the Section “Energy associated with the SNWD project and water end use”) whether the EFW at household level should be included or not in the calculation of the total EFW chain (Hu et al , 2013).…”
Section: Resultscontrasting
confidence: 60%
“…This value did not include the EFW end use at household level (e.g., the energy for heating water, running washing machines, or dishwashers). A previous study by Li (2012) estimated the household-level EFW of Beijing in 2010 as 4.88 billion kWh, which is greater than the EFW in this study. But it is still debated (see the Section “Energy associated with the SNWD project and water end use”) whether the EFW at household level should be included or not in the calculation of the total EFW chain (Hu et al , 2013).…”
Section: Resultscontrasting
confidence: 60%
“…Jensen conducted a questionnaire survey of 632 visitors at 4 attractions in Norway and found that visitor perceptions varied significantly depending on the attraction and type of visit [ 12 ]. Li used cognitive maps and supplemented them with questionnaires to obtain participants’ perceptions of space and found that students had a high perception preference for historical spaces [ 38 ]. However, these types of studies are expensive and time-consuming and are limited to research with specific sample conditions.…”
Section: Literature Reviewmentioning
confidence: 99%